2016
DOI: 10.7717/peerj.1663
|View full text |Cite
|
Sign up to set email alerts
|

LPS- orPseudomonas aeruginosa-mediated activation of the macrophage TLR4 signaling cascade depends on membrane lipid composition

Abstract: It is well known that PUFA impede the LPS-mediated activation of the transcription factor NFkappaB. However, the underlying mode of action has not been clarified yet. To address this issue in a comprehensive approach, we used the monocyte/macrophage cell line RAW264.7 to investigate the consequences of a PUFA supplementation on the TLR4 pathway with a focus on (i) the gene expression of TLR4 itself as well as of its downstream mediators, (ii) the membrane microdomain localization of TLR4 and CD14, (iii) the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
5
31
0
5
Order By: Relevance
“…BAMBI was a TGF-β pseudoreceptor ,and down-regulation of BAMBI made HSCs beccome more sensitive to TGF-β [18], that was the main mechanism of endotoxin-induced hepatic brosis [19,20]. HSCs was the naïve cells that responds to LPS by TLR4 [21], BAMBI was down-regulated after TLR4-MyD88-NF-κB pathway was activated in HSCs [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAMBI was a TGF-β pseudoreceptor ,and down-regulation of BAMBI made HSCs beccome more sensitive to TGF-β [18], that was the main mechanism of endotoxin-induced hepatic brosis [19,20]. HSCs was the naïve cells that responds to LPS by TLR4 [21], BAMBI was down-regulated after TLR4-MyD88-NF-κB pathway was activated in HSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Activated HSCs expresses TLR4 and had a higher response to LPS [21]. LPS was a de nitive ligand of TLR4, it activated HSCs through the MyD88-NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mechanisms associated with this process have remained elusive until recently. In an elegant paper by Schoeniger and colleagues, the authors demonstrated that, unlike the predicted mechanism at the level of gene expression, PUFA enrichment affects TLR4 at the membrane [26**]. In fact, the findings provide evidence that PUFAs can disrupt PM microdomains and significantly impair stimulation of TLR4 [27].…”
Section: Extent Of Phospholipid Saturation and Cell Signalingmentioning
confidence: 99%
“…Возбуждение РАМР Pseudomonas aeruginosa TLR альвеолярных макрофагов приводит к секреции ими провоспалительных цитокинов (TNF α, IL 6) и некоторых хемокинов, в част ности макрофагального провоспалительного протеина 1α (CCL3/MIP 1α), активно рекрутирующего нейтрофилы [78,84] [44]. Также у людей с нейтропенией, обусло вленной химиотерапией, наблюдается высокая частота встречаемости синегнойной инфекции [50].…”
Section: макрофаги и альвеолярные макрофагиunclassified